The Cultural Evolution of Roma Population in Romania: From the Inter-War Period to Ceausescu Dictatorship - Villa, Eliana (Richtmann Publishing, 2012)
Since the Middle Age, when we have the first sources about the presence of the Gypsy community in Romania, theRoma population occupied a marginality place. The slavery, which they were subjects to since the XIV and XV centuries in theprincipalities of Wallachia and Moldavia, determined, as direct consequence, the placement of Roma in an inferior social positionand discrimination by the attitude of the Romanian population. This former condition of inferiority is necessary to understand themotivations that have determined such a little attention to the Roma and to the respect for its rights and its culturalcharacteristics. This is especially true by the end of the WW I, when Romania became a big country with a large territory andmany populations to rule. Since this time the Roma will suffer the politics of homogenization to the majority population andconsequent loss of cultural characteristics. Nevertheless during the interwar age there were attempts to preservations of identitycarried by some associations defending the rights of Roma .But these associations were suppressed in 1938, by theauthoritarian resolution of Carol II and then, in 1940, when Antonescu established the military dictatorship, any identity rights toRoma were denied: anyone who refused the homogenization was deported to Transnistria. Afterwards, in communist age, until1989, Roma were considered only as Romanian people, and therefore forced to live as the majority population. However theattitudes of discriminations against them did not stop, thus the Roma were not able to rise socially. In Romania today asignificant part of the Roma still lies in poverty, unemployment and illiteracy condition and it’s still considered the scum ofsociety. Trough the study of the history of Roma, we can understand the reasons of their diversity and the difficult integration inEuropean societies.